SUPERVISI KLINIS SEBAGAI UPAYA PENINGKATAN KOMPETENSI GURU PAI - Lahmi, Ahmad; Arman, Iza; Mursal, Mursal (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2021)
Teachers' ability must be continuously improved because they are as a benchmark of the quality of education, a form of teacher improvement in state-shaped educational institutions has many varied forms, this is different from that obtained by private educational institutions such as Private MTs Istiqamah Talu. This study aims to describe how clinical supervision is carried out in Private MTs Talu as an effort to improve the competence of Islamic Religious Education teachers. For the achiever of this goal, this research was designed using qualitative approach, while the research data source consists of madrasah head, supervisor and PAI teacher, to obtain data from the source that has been determined by researchers using observation techniques, interviews and documentation studies, research data is analyzed descriptively. From the results of the research it is known that the implementation of clinical supervision of PAI teachers starts from the preliminary stage, implementation and feedback stage, clinical supervision activities can improve the competence of PAI teachers, especially professional competencies.